Pluralisme Hukum dalam Pembagian Waris: Studi Sosio-Humaniora pada Masyarakat Indonesia - Vivi Sylvia Purborini; Jusrihamulyono (Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Riau, 2026)
This study aims to analyze legal pluralism in inheritance distribution within Indonesian society through a socio-humanities approach. Indonesia, as a country with diverse cultures and legal systems, recognizes legal pluralism consisting of customary law, Islamic law, and Western civil law. This diversity creates dynamic and varied practices in inheritance distribution that are not always uniform. The research employs a qualitative method with a socio-legal approach, using literature review and analysis of existing social practices. The findings reveal that legal pluralism provides flexibility for communities in choosing the legal system applied in inheritance distribution. However, this condition also has the potential to generate conflicts, particularly when there are differences in interests among parties or misunderstandings of applicable legal norms. Furthermore, social, cultural, and religious factors significantly influence the selection of legal systems within society. Therefore, legal harmonization and contextual approaches are necessary to minimize conflicts and achieve substantive justice in inheritance distribution in Indonesia.